Mechanical and Thermo-Mechanical Behaviors of Cork Filler-Reinforced Epoxy Composite - Parthasarathy Chandramohan; Mayandi Kalimuthu; Karthikeyan Subramanian; Rajini Nagarajan; Faruq Mohammad; Hamad A. Al-Lohedan; Kumar Krishnan; Sikiru O. Ismail (BioResources)
Mechanical characteristics were studied for epoxy composites reinforced with cork fillers, analyzing various loading conditions of fillers ranging from 0 to 30%. The fabrication utilized a hand layup method. The results indicated that the composite mechanical properties, glass transition temperature, and storage modulus were optimal at a 20% natural filler loading. Dynamic mechanical analysis (DMA) showcased exceptional energy absorption capabilities up to 110 °C. Thermogravimetric analysis (TGA) showed that the bio-filler degraded quickly, leaving 0.3% remnant, but the cork filler composite (25% v/v) showed an even residue concentration of 9%. Additionally, biodegradability tests showed weight loss in a soil burial test with the addition of bio-filler to the composite.